PENGARUH BEBAN KERJA DAN STRESS KERJA TERHADAP KINERJA PEGAWAI MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA PT. PEGADAIAN SYARIAH CABANG BANGKALAN - Tyas, Dyah Ayu Hananing; Prasetyo, Indra (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2024)
This research aims to find out how workload and work stress influence employee performance at PT. Pegadaian Syariah Bangkalan Branch through job satisfaction. The data analysis technique uses PLS (Partial Least Square) structural equation modeling analysis with the SmartPLS version 3.0 program. Validity and Reliability Test. The results of this research state that 1) There is a significant positive influence of Workload on Job Satisfaction 2) There is an insignificant positive influence of Job Stress on Job Satisfaction 3) There is a significant positive influence of Workload on Employee Performance 4) There is a positive influence which is not significant from Job Stress to Employee Performance 5) There is an insignificant positive effect of Job Satisfaction on Employee Performance 6) There is a positive, significant mediation of Job Satisfaction on the effect of Workload on Employee Performance 7) There is positive but not significant mediation of Job Satisfaction significant influence of Job Stress on Employee Performance.